Evaluating the Stanford Diagnostic Reading Test as a measure of reading comprehension and vocabulary for South African grade eight learners. - Catto, Deborah Diane (My University, 2010)
One of the needs of assessment practitioners in South Africa is for the adaptation or revision of current psychological and educational tests to justify their use in the South African context. The South African Department of Education called for the re-evaluation of all standardised tests used in the South African context (Department of Education, 1997). The Stanford Diagnostic Reading Test (SDRT) is an English language proficiency test that is useful in measuring reading comprehension. The fact that English is the language of instruction in most South African schools makes the SDRT a valuable measure for South African assessment practitioners. This study evaluated the SDRT as a measure of vocabulary and reading comprehension for South African Grade Eight learners on the basis of home language and gender. Two subtests (Auditory Vocabulary and Reading Comprehension) of the Brown level of the SDRT were administered to three consecutive years of Grade Eight learners. Of 631 subjects, all of who had received at least five years of English medium education, 279 were English First Language (EFL) learners and 352 were English Additional Language (EAL) learners. There were 316 male subjects and 315 female subjects. The results showed that the EAL learners performed significantly below the EFL learners on both the Vocabulary and Reading Comprehension subtests of the SDRT. There was also a significant difference in performance between male and female learners on the Comprehension subtest but not on the Vocabulary subtest. Both the Vocabulary and the Reading Comprehension subtests demonstrated adequate internal consistency. However, the validity of these subtests was questioned because a number of items appeared to demonstrate bias against EAL learners.